Antiplasmodial, Antioxidant and Cytotoxicity Activity of Ethanol and Aqueous Extracts of Khaya grandifoliola Stem Bark - Gamago Nkadeu Guy-Armand; Yamssi Cedric; Noumedem Anangmo Christelle Nadia; Mounvera Abdel Azizi; Ngouyamsa Nsapkain Aboubakar Sidiki; Tientcheu Noutong Jemimah Sandra; Tako Djimefo Alex Kevin; Vincent Khan Payne (Journal of Tropical Medicine, 2023)
Background. Malaria is a serious public health problem, especially in sub-Saharan Africa. The aim of this study was to scientifically provide baseline information on the use of Khaya grandifoliola stem bark as an antimalaria drug by traditional healers. Method. The stem barks of K.grandifoliola were harvested and dried to obtain powder, and fifty grams of the powder were soaked in ethanol and hot distilled water respectively, for the preparation of ethanol and aqueous extracts, then dried in an oven at 40°C for the ethanol extract and 50°C for the aqueous extract. Plasmodium falciparum strains 3D7 sensitive and Dd2 resistant to chloroquine, were used to evaluate in vitro antiplasmodial activity using SYBR Green. The ability of the extracts to prevent oxidative stress was assessed by trapping 2, 2′-diphenyl-1-picrylhydrazyl (DPPH); nitric oxide, hydrogen peroxide and ferric reducing power. The cytotoxicity test of the extracts was carried out on RAW 264.7 cell lines and on erythrocytes. The data obtained were entered in the Excel software, then in Graph pad where the IC50 was calculated and the curves plotted. Results. The fifty percent inhibition (IC50) of the antiplasmodial activity of the chloroquine-resistant strain PfDd2 were 54.27 ± 2.41 μg/mL and 31.19 ± 4.06 μg/mL respectively, for the aqueous and ethanol extracts. As for the Chloroquino-sensitive Pf3D7, IC50 of 53.06 μg/mL was obtained for the aqueous extract and 28.03 ± 1.90 μg/mL for ethanol. The DPPH radical scavenging activity presented IC50 of 104 μg/mL for the aqueous and 2.617 μg/mL for the ethanol extract; for the Nitric oxide (NO) presented an IC50 of 301 ± 21 μg/mL for the aqueous extract 140.7 ± 21 μg/mL for the ethanol; for hydrogen peroxide the ethanol and aqueous presented IC50 of 845.1 ± 21 μg/mL and 509.4 ± 21 μg/mL respectively. The cytotoxicity on RAW 264.7 cells presented High CC50 in particular >1000 μg/mL and 467.4 μg/mL respectively for the aqueous and ethanol extract. Conclusion. Extracts of Khaya grandifoliola exhibited antiplasmodial activity. The ability to inhibit oxidative stress as well as lower cell toxicity on RAW 264.7 and erythrocytes, is a good indicator. However, in vivo tests remain important in order to confirm the use of this plant for the treatment of malaria.